Geographic Distribution, Flight Phenology and Infestation Level of the Lepidopteran Pests Euhyponomeutoides albithoracellus, Lampronia capitella and Synanthedon tipuliformis on Black Currants in Northern Europe - Svensson, Glenn P.; Huynh, Hanh; Isaksson, Ann‐Kristin; Myhre, Line Beate Lersveen; Löfstedt, Christer; Mogan, Sigrid; Öberg, Elisabeth; Rantanen, Marja; Trandem, Nina; Anderbrant, Olle (Wiley-Blackwell, 2025)
The currant bud moth, Euhyponomeutoides albithoracellus, the currant shoot borer, Lampronia capitella and the currant clearwing, Synanthedon tipuliformis, are destructive pests on currants in the Nordic countries, but detailed information about their relative abundance in commercial crop fields is lacking. We used pheromone-baited monitoring traps to analyse the presence and flight period of the three species in 28 commercial black currant fields in Finland, Norway and Sweden during 4 years. We also estimated moth-induced damage in the same fields and analysed within- and between-generation relationships of catches and damage to find patterns to predict current and future pest pressures. At least two of the species were found at all sites. The shoot borer was the most widespread and abundant species, followed by the clearwing, which was relatively common at all sites except in northern Sweden, whereas the bud moth was not detected at all in Norway and southern Sweden. Geographic variation in flight phenology was observed for both the shoot borer and the clearwing. We found a significant positive correlation in all between-year analyses of damage and in most between-year analyses of catches, but a less consistent pattern when relating catches to damage within and between generations. Combining catch and damage data may be a useful tool to predict future overall infestation levels of the three pests in black currant fields in the Nordic countries.
Keywords: crop damage; Lepidoptera; monitoring; pest management; pheromone trap; Ribes nigrum